Azab Kaum Lūt Dalam Al-Qur’an (Kajian Kisah Berbasis Tafsir ‘Ilmī) - Muhammad Nuril Fauzan (JIA (Jurnal Ilmu Agama), 2023)
Thearchaeologicalfindings at Tall el-Hammam are often associated with evidence of a catastrophic event during the time of the Lūṭ's destruction. The Qur'an describes this event as a warning to future generations, and the discoveries made can be correlated with the Qur'an and studied urgently. This qualitative research project utilized library research techniques to explore how the events described in the Qur'an can be discussed in scientific discourse. Three forms of doom are identified, including lightning sounds, earth turning, and stone rain, which can be researched through the scientific lens of mufasir 'Ilmi. Some believe the event was caused by an erupting mountain, while others argue it was the result of a meteor shower. This study aims to demonstrate the relationship between scholarly interpretation and the scientific discoveries at Tall el-Hammam.